2003
DOI: 10.1002/masy.200350716
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of rigid polyurethane foams derived from sodium lignosulfonate mixed with diethylene‐, triethylene‐ and polyethylene glycols

Abstract: Sodium salt of lignosulfonic acid (LS), which was obtained as by‐product of cooking process in sulfite pulping, was solved in diethylene, triethylene or polyethylene glycol. Three series of polyurethane foams (LSPU) were synthesized by varying the LS content from 0 to 33 wt%. Apparent density (ρ) of LSPU foams ranged from 0.08 to 0.18 g cm−3 and was affected by both LS content and oxyethylene chain length. Glass transition temperatures increased with increasing amount of LS and with decreasing oxyethylene chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
2
22
0
2
Order By: Relevance
“…In general, the results were in agreement with the data found for biopolyol-based PUR (Hakim et al 2011). However, Hatakeyama et al (2003) found that Tg increased with increasing lignosulfonate content. Outstanding results were found for the reference PPG-based (REF) and HZ2 (PPG/HZ = 0.7/0.3 w/w) foams exhibiting Tg = 100 °C.…”
Section: Fig 2 Sem Micrographs Of the Investigated Foamsmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, the results were in agreement with the data found for biopolyol-based PUR (Hakim et al 2011). However, Hatakeyama et al (2003) found that Tg increased with increasing lignosulfonate content. Outstanding results were found for the reference PPG-based (REF) and HZ2 (PPG/HZ = 0.7/0.3 w/w) foams exhibiting Tg = 100 °C.…”
Section: Fig 2 Sem Micrographs Of the Investigated Foamsmentioning
confidence: 95%
“…From the statistical analysis it was found that an increasing content of HZ lignin resulted in an increased 1 st degradation temperature. The major decomposition starts at approximately 280 °C, which corresponds to the dissociation of urethane linkages formed from phenolic hydroxyls (Hatakeyama et al 2003). The effect of PPG, glycerol, and HZ on T50% was the opposite.…”
Section: Fig 2 Sem Micrographs Of the Investigated Foamsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have suggested that the performance of lignin and PU products may be improved by the addition of other polyols, such as polyethylene glycol (PEG), polypropylene glycol (PPG) (Saraf et al 1985;Mörck et al 1988), and other chain lengths of polyether polyols, during the copolymerization process (Hatakeyama et al 2003). The addition of PEG and PPG affected the flexibility and rigidity of the PU.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin-based PU synthesis requires catalysts and additives as shown in Scheme 2. Typical additives are poly(ethylene glycol) (PEG), 34,98,99 poly(caprolactone) 100 and diethylene glycol. 101 The additives are used to prevent brittleness of the PU by adding soft segments in the PU network structure.…”
Section: Lignin-based Polymersmentioning
confidence: 99%